Challenged hegemony : the United States, China, and Russia in the Persian Gulf - Yetiv, Steven A.; Oskarsson, Katerina, 1983- (Stanford University Press, 2018)
This book examines how the rise of U.S. hegemony in the Persian Gulf, and changes in the position of China and Russia over 45 years, have boosted global oil security, even as American hegemony and influence continue to face challenges.